Photosynthetic activity buffers ocean acidification in seagrass meadows - I. E. Hendriks; Y. S. Olsen; L. Ramajo; L. Basso; A. Steckbauer; T. S. Moore; J. Howard; C. M. Duarte (Biogeosciences, 2014)
Macrophytes growing in shallow coastal zones characterised by intense metabolic activity have the capacity to modify pH within their canopy and beyond. We observed diel pH changes in shallow (5–12 m) seagrass ( Posidonia oceanica ) meadows spanning 0.06 pH units in September to 0.24 units in June. The carbonate system (pH, DIC, and aragonite saturation state (Ω Ar )) and O 2 within the meadows displayed strong diel variability driven by primary productivity, and changes in chemistry were related to structural parameters of the meadow, in particular, the leaf surface area available for photosynthesis (LAI). LAI was positively correlated to mean, max and range pH NBS and max and range Ω Ar . In June, vertical mixing (as Turbulent Kinetic Energy) influenced max and min Ω Ar , while in September there was no effect of hydrodynamics on the carbonate system within the canopy. Max and range Ω Ar within the meadow showed a positive trend with the calcium carbonate load of the leaves, pointing to a possible link between structural parameters, Ω Ar and carbonate deposition. Calcifying organisms, e.g. epiphytes with carbonate skeletons, may benefit from the modification of the carbonate system by the meadow. There is, however, concern for the ability of seagrasses to provide modifications of similar importance in the future. The predicted decline of seagrass meadows may alter the scope for alteration of pH within a seagrass meadow and in the water column above the meadow, particularly if shoot density and biomass decline, on which LAI is based. Organisms associated with seagrass communities may therefore suffer from the loss of pH buffering capacity in degraded meadows.